1996
DOI: 10.1055/s-2007-973761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course, Early Diagnosis, Treatment, and Prevention of Disease in Glutaryl-CoA Dehydrogenase Deficiency

Abstract: In presymptomatic children with GDD, the onset of neurological disease can be prevented by vigorous treatment of catabolic crises during illnesses together with carnitine supplementation. The importance of dietary therapy remains unclear and needs further evaluation. The potential treatability of GDD calls for increased attention to early presenting signs in order to recognize the disorder and to initiate treatment before the onset of irreversible neurological disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
222
1
26

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(254 citation statements)
references
References 0 publications
5
222
1
26
Order By: Relevance
“…In the other symptomatic patients, no acute encephalopathic crises were reported. Thirty-four of them were classified as insidious onset (6,19) and five as late onset (22,23); five patients remained unclassified. Patients with late onset type were not treated specifically before diagnosis, and were diagnosed only after symptoms supervened.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the other symptomatic patients, no acute encephalopathic crises were reported. Thirty-four of them were classified as insidious onset (6,19) and five as late onset (22,23); five patients remained unclassified. Patients with late onset type were not treated specifically before diagnosis, and were diagnosed only after symptoms supervened.…”
Section: Study Populationmentioning
confidence: 99%
“…Strikingly, acute encephalopathic crises, which are precipitated by intercurrent febrile illnesses and primarily affect the striatum (18 -20), usually manifest during infancy (3,19,21). However, late-onset neurologic disease has recently been described (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The histogenesis of PRC is still unclear. Five major hypotheses have been advocated: heterotopic ovarian tissue 2 , monodermal variant of teratomas 3 , embryonic urogenital remnants 4 , intestinal duplications 5 and celomic metaplasia 6 . In our case, histological and immunohistochemical analyses concluded that the PRC developed from an extraovarian Müllerian issue.…”
Section: Primary Retroperitoneal Endometrial Cystadenocarcinoma Presementioning
confidence: 99%
“…Typically, GA1 presents in later infancy as an acute encephalopathy with predominant dystonia and dyskinesia due to necrosis of the basal ganglia, particularly affecting the putamina [19]. However, neonates may present with macrocephaly and subtle neurological signs such as hypotonia, irritability and jitteriness.…”
Section: Glutaric Aciduria Typementioning
confidence: 99%